Analisis Prosedur Pembiayaan Mudharabah Pada Bank Bsi Kc Surabaya (Analysis Mudharabah Financing Procedures Of Bank Bsi Kc Surabaya) - Syafrida Maulidyah; Fauzatul Laily Nisa (Jurnal Ekonomi dan Bisnis Digital, 2024)
A contract is a relationship or meeting of agreement and acceptance which gives rise to regulatory consequences. The mudharobah agreement is a cooperation agreement signed by the fund owner (Shohibul Mall) with the fund manager (Mudhorib), where profits are generated in accordance with the agreement made before the agreement. The purpose of this writing is to understand mudharabah financing according to OJK fatwas and standards, procedures and requirements for applying for mudharabah financing at BSI KC Surabaya further. Apart from that, so that prospective customers know the easy financing procedures using the Mudhorobah Agreement so that they can absorb more customers. The research uses qualitative with a library research method which is descriptive by means of analysis.